Beyond COP28: Brazil must act to tackle the global climate and biodiversity crisis - Flávia de Figueiredo Machado; Marcela C. N. S. Terra; André Ferreira Rodrigues; Philip M. Fearnside; Luís Fernando Guedes Pinto; Polyanna da Conceição Bispo; Frederico V. Faleiro; André G. Coutinho; André Luis Regolin; Carolina Jaramillo-Giraldo; Fabiano R. Melo; Felipe P. L. Melo; et al. (npj Biodiversity)
Extreme weather has made 2023 virtually certain to be the warmest year on record, signaling unprecedented climate and biodiversity crises. Brazil, the world’s most biodiverse country, with two hotspots and complex social and economic layers, has experienced escalating environmental degradation over the past years. Alarming rates of native vegetation loss, wildfires, severe and prolonged droughts, and heatwaves have adversely impacted several Brazilian ecosystems and societies. Despite the country’s decisive role in global carbon neutrality, bridging the gap between Brazil’s discourse on the international stage and its concrete actions at home remains a significant challenge. This correspondence, a collective plea from scientists across various sectors, underscores the urgent imperative for national engagement and commitment to halt and mitigate these crises. We aim to catalyze a robust international public debate, influencing Brazilian decision-makers to chart a concrete sustainable pathway. Aligned with global initiatives, we emphasize the crucial interplay between national and international efforts in combating climate change and the conservation of biodiversity and socio-biodiversity.